Superior enhancement in thermal conductivity of epoxy/graphene nanocomposites through use of dimethylformamide (DMF) relative to acetone as solvent - Swapneel Danayat; Avinash Singh Nayal; Fatema Tarannum; Roshan Annam; Rajmohan Muthaiah; Madhan K. Arulanandam; Jivtesh Garg (MethodsX, 2023)
This method article describes the fabrication of graphene-epoxy nanocomposites using two different solvents, dimethylformamide (DMF) and acetone, and validates the resulting thermal conductivity improvements. The study compared the two solvents at a filler composition of 7 wt% and found that DMF resulted in more uniform dispersion of graphene nanoparticles in the epoxy matrix, leading to a 44% improvement in thermal conductivity compared to acetone. Laser scanning confocal microscopy (LSCM) imaging showed that DMF-based composites had more evenly dispersed graphene nanoplatelets than acetone-based composites, which exhibited larger graphene agglomerations. Effective medium theory calculations showed that DMF led to almost 35% lower interface thermal resistance between graphene and epoxy compared to acetone. The validated fabrication method and findings provide new possibilities for developing high thermal conductivity graphene-epoxy nanocomposites for various thermal management applications. • This article describes methods for fabricating graphene-epoxy composites using acetone and DMF as solvents, and validates that DMF is better for achieving higher thermal conductivity in the composite.